THE EFFECT OF JOB CRAFTING AND SELF EFFICACY ON EMPLOYEE PERFORMANCE WITH WORK ENGAGEMENT AS AN INTERVENING VARIABLE (STUDY ON PLTU SALIRA 1X660 MW PT LESTARI BANTEN ENERGI) - Rizki, Khoirul; Prahiawan, Wawan (Ridwan Institute, 2024)
This study aims to test and analyze the influence of employee job crafting and self-efficacy to increase work engagement and improve employee performance. 126 respondents of PT Lestari Banten Energi were selected for the study. The measurement model test in this study was carried out. The structural model was evaluated using R-square for the dependent variable, the Stone geisser Q-square test for predictive relevance, and the t-test to assess the significance of the structural path parameter coefficient. The results showed that (1) there is a positive and significant influence of job crafting on the work engagement of employees, so that the higher the job crafting of employees owned, the better the performance will be. (2) There is an influence of work engagement on the performance of employees because the Tstatic (3,957) > Ttable (1.96) and Pvalue (0.000) sig (0.05) values. (3) There are two factors that mediate the positive influence of the two factors: (1) job crafting, (2) work engagement, and (3) work engagement.